Integrasi Ilmu Pengetahuan dan Pendidikan Islam: Menjembatani Kesenjangan antara Sains dan Agama - M. Yusuf (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This research aims to explain the importance of integrating science and Islamic education in building a harmonious relationship between science and religion. The background lies in the differences in perspectives and conflicts that often arise between science and religion, leading to gaps in understanding the world and differing values. The objective of this study is to analyze the concept of integrating science and Islamic education and explore strategies to bridge these gaps. The research method employed is library research, which involves collecting and analyzing data from relevant literature sources. The findings of this study reveal that the integration of science and Islamic education plays a crucial role in creating a comprehensive and sustainable understanding of the world. The identified strategies to achieve this goal include interdisciplinary approaches, the development of integrated curricula, contextual learning, interdisciplinary dialogues, research and development, teacher training, and the utilization of relevant educational resources. It is expected that the integration of science and Islamic education will bring benefits in building holistic understanding, fostering spiritual awareness, and preparing individuals for open and comprehensive thinking.